Diversité floristique et caractéristiques structurales des groupements végétaux du bassin du Zio (Sud-Togo) - Essowazina Seou; Laounta Akame; Tchaa Boukpessi (Physio-Géo)
The Zio basin is a geographical area that abounds in great biological diversity. It has a rich and diverse flora whose characteristics must be determined from a sustainable management perspective. To do this, a methodological approach based on the collection of floristic and dendrometric data made it possible to identify 371 plant species, belonging to 271 genera and 82 families. The overall biological spectrum shows the predominance of phanerophytes. In this group, we see the abundance and dominance of microphanerophytes with an abundance of 46.15 % and a dominance of 33.03 %. Followed by nanophanerophytes (17.59 % of the raw spectrum and 23.99 % of the weighted spectrum) and microphanerophytes (8.58 % of the raw spectrum and 4.37 % of the weighted spectrum). Depending on phytogeographical affinities, the plant formations of the large Zio basin are dominated by species found both in the Guinean-Congolese and Sudano-Zambezian zones. They are the most abundant (42.35 %) and the most dominant (33.66 %). They are followed by the Guinean-Congolese species (24.59 % of the raw spectrum and 32.83 % of the weighted spectrum), and Sudano-Zambezian species (14.69 % of the raw spectrum and 9.37 % of the weighted spectrum). The ordination of the records made it possible to discriminate four plant groups, namely: the grouping with Pterocarpus erinaceus and Adansonia digitata; the grouping with Daniellia oliveri and Anogeissus leiocarpa; the grouping with Mitragyna Inermis and Cynometra megalophylla; and the grouping with Khaya grandifoliola and Cola gigantea. The structural analysis of the different groupings shows a predominance of individuals of small diameter and medium to low height. This great floristic wealth deserves to be preserved through a sustainable and efficient management plan.